Створення Євразійського кластера залізничного транспорту для підвищення професіонально-наукового потенціалу - Чеклов, Володимир; Подкользіна, Катерина (Видавництво Львівської політехніки, 2013)
The task of this article is an analysis of position of the railway industry in the Euro-Asian space, getting the effect of the creation in Euro-Asian cluster of railway universities. Combining science at a European and Asian universities cluster rail transport will have at its disposal a strong base in the rail sector. This will not only best use of human resources, research and development, but also will promote rail transport market to a whole new level. Competition between roads remain as such, the cluster is not a monopoly, but its creation greatly strengthen weaknesses in the scientific aspect of employment in many countries, and enhance overall competitiveness of rail transport in Europe and Asia to other modes of transport, improve and simplify the interaction of both legally and technologically.
Keywords: кластер; обмін досвідом; модель навчання; науковий потенціал; кваліфікація